Evaluating hepatotoxic effects of chemotherapeutic agents with gadoxetic-acid-enhanced magnetic resonance imaging. Issue 124 (March 2020) - Theilig, Dorothea; Elkilany, Aboelyazid; Jann, Henning; Roderburg, Christoph; Hamm, Bernd; Fehrenbach, Uli; Geisel, Dominik
Highlights: Gadoxetic-acid-enhanced MRI can be used as an imaging-based liver function test. Hepatotoxicity of chemotherapy can be determined with gadoxetic-acid-enhanced MRI. Hepatotoxicity of current chemotherapy for neuroendocrine tumours is underscored. Abstract: Purpose: To evaluate the hepatotoxicity of different chemotherapeutic agents used to treat neuroendocrine tumours (NETs) with gadoxetic acid-enhanced magnetic resonance imaging (MRI). Material and methods: A total of 129 patients with NETs who underwent two or more serial gadoxetic-acid-enhanced MRI examinations between 2014 and 2018 and started chemotherapy in the beginning of that time period were retrospectively analysed. Linear mixed model analysis evaluating relative enhancement (RE) of the liver in the hepatobiliary phase with respect to time between MRI examinations, primary chemotherapy, hepatotoxicity score of preceding and subsequent chemotherapies as well as age and gender as fixed variables was performed. Binary logistic regression was used to verify whether the hepatotoxicity score predicts a significant impact of a chemotherapeutic regimen on RE and hence liver function. Results: Linear mixed model analysis of a total of 539 MRI examinations identified all chemotherapeutic agents with known hepatoxicity as a factor with a statistically significant negative impact on RE of the liver in gadoxetic-acid-enhanced MRI in addition to age. This result was confirmed by binary logistic regression analysis. Conclusion: Our results confirm that gadoxetic acid-enhanced MRI can be used as an imaging-based liver function test for assessing hepatotoxicity of chemotherapeutic agents used for NETs. The findings underscore the known degrees of hepatotoxicity of the chemotherapeutic agents currently used in the treatment of NETs.